Biliopancreatic Diversion: The Effectiveness of Duodenal Switch and Its Limitations - Blaire Anderson; Richdeep S. Gill; Christopher J. de Gara; Shahzeer Karmali; Michel Gagner (Gastroenterology Research and Practice)
The prevalence of morbidly obese individuals is rising rapidly. Being overweight predisposes patients to multiple serious medical comorbidities including type two diabetes (T2DM), hypertension, dyslipidemia, and obstructive sleep apnea. Lifestyle modifications including diet and exercise produce modest weight reduction and bariatric surgery is the only evidence-based intervention with sustainable results. Biliopancreatic diversion (BPD) produces the most significant weight loss with amelioration of many obesity-related comorbidities compared to other bariatric surgeries; however perioperative morbidity and mortality associated with this surgery are not insignificant; additionally long-term complications including undesirable gastrointestinal side effects and metabolic derangements cannot be ignored. The overall quality of evidence in the literature is low with a lack of randomized control trials, a preponderance of uncontrolled series, and small sample sizes in the studies available. Additionally, when assessing remission of comorbidities, definitions are unclear and variable. In this review we explore the pros and cons of BPD, a less well known and perhaps underutilized bariatric procedure.